PROFIL KLINIS ESODEVIASI DI PUSAT PELAYANAN KESEHATAN TERSIER - Nursalim, Ade J.; Latun, Erick; Poluan, Herny (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: Esodeviation is an ocular anomaly in which the visual axis has a manifest or latent misalignment. Diagnosis of this anomaly needs a further thorough examination of an ophthalmologist. This study was aimed to obtain the profile of esodeviation patients at Ophthalmology Clinic of Prof. Dr. R. D. Kandou Hospital Manado. This was a descriptive retrospective study using the medical record data of patients with esodeviation from January 2014 to August 2017. There were 21 patients with esodeviation during that period of time, consisted of 13 males (61.9%) and 8 females (38.1%). The age range was 1-12 years old with the highest percentage in 5 years old (16 patients; 76.1%). The esodeviation types were esotropia accounted in 15 patients (71.4%) and esophoria in 6 patients (28.6%). Refraction anomalies were the most common etiology of esodeviation (57.1%). Squint was the main complaint (61.9%) and 22 degree prism was the most deviation degree (66.7%). Conclusion: In this study, esodeviation was most common in males, age under 5 years, esotropia type, squint as the main complaint, with refraction anomaly as the main cause, and deviation less than 22 degrees prism.Keywords: esodeviation, esotropia, esoforia, etiology, deviation degreeAbstrak: Esodeviasi adalah keadaan dimana aksis visual tidak lurus baik manifes maupun laten. Diagnosis esodeviasi memerlukan pemeriksaan lebih lanjut dari seorang dokter ahli mata. Penelitian ini bertujuan untuk mendapatkan profil klinis esodeviasi di Poliklinik Mata RSUP Prof. Dr. R. D. Kandou Manado dengan menggunakan data rekam medik pasien dari Januari 2014 hingga Agustus 2017. Hasil penelitian mendapatkan sebanyak 21 pasien, terdiri dari 13 pasien (61,9%) laki-laki dan 8 pasien (38,1%) perempuan. Rentang usia berkisar 1-12 tahun dengan usia terbanyak di bawah 5 tahun sebanyak 16 pasien (76,1%). Tipe esodeviasi terbanyak ialah esotropia sebanyak 15 pasien (71,4%) dan esoforia sebanyak 6 pasien (28,6%). Etiologi terbanyak ialah kelainan refraksi (57,1%). Keluhan utama pasien berobat ialah mata terlihat juling (61,9%) dan derajat deviasi terbanyak ialah kurang dari 22 derajat prisma (66,7%). Simpulan: Pada penelitian ini, esodeviasi terutama dijumpai pada jenis kelamin laki-laki, usia <5 tahun, tipe esotropia, keluhan mata juling, dengan etiologi kelainan refraksi, dan derajat deviasi <22 derajat prisma.Kata kunci: esodeviasi, estotropia, esoforia, etiologi, derajat deviasi